HPV vaccination and allocative efficiency: regional analysis of the costs and benefits with the bivalent AS04-adjuvanted vaccine, from the perspective of public health, for the prevention of cervical cancer and its pre-cancerous lesions - Bonanni, Paolo; Panatto, Donatella; Dirodi, Bruna; Boccalini, Sara; Gasparini, Roberto (Farmeconomia. Health economics and therapeutic pathways, 2012)
Introduction: by means of the decisions on whether to introduce the HPV vaccination, Public Health has already established the importance of associating the vaccination strategy to the policy of secondary prevention. The screening + vaccination strategy is more effective than the two methods taken individually. In support of this combined strategy and in order to make available per each region concrete elements for their regional planning, an assessment has been made, which also takes into account the effect of cross-protection regarding high-risk strains not contained in both vaccines, bivalent and quadrivalent, and more frequently responsible for pre-cancerous lesions and cervical cancer (CCU). This analysis evaluates the costs and benefits of screening + vaccination strategy in a 12-year-old female cohort. Furthermore, the paper provides results that may be useful to assess the opportunity to extend the vaccination to a second cohort of 24-25-year-old women. The analysis is preceded by a brief summary of CCU epidemiology available data, public health policies that give precise guidelines for vaccination strategies and analytical tools suitable to support public policy makers to efficiently allocate resources. Methods: two different models were used for two regional analyses.The vaccines may have different sustained- and cross-protection levels against non-vaccine oncogenic HPV-types. In the first analysis, a prevalence-based model estimated the potential net difference in HPV-related lesions (abnormal pap smear, cervical intraepithelial neoplasia (CIN), cervical cancer (CC) and genital warts (GW)) and associated costs generated by the two vaccines. Vaccine efficacy rates were based on published data for each vaccine. Lifetime vaccine efficacy was assumed. Results are reported over one year after reaching a steady state. Incidence and treatment costs were obtained from Italian and European sources. We also performed a cost-effectiveness analysis with a Markov model for each Italian region, previously described and successfully adapted to the national scenario. The analysis compares the HPV vaccination of a single cohort (12-year-old females) with a multiple cohort (12- + 25-year-old girls). Resource use was based on a standard therapeutic path applied to all regions. However we quantified the impact of the so-called “decentralization progress” by collecting regional data on: pap test coverage, tariffs for treatments, and cost of the vaccination course. Results: the results are set out in 21 regional reports. Conclusions: in the Italian scenario, characterized by decentralization and local autonomy, a further level of detail is essential in order to describe the specific local settings and implications of a new health intervention. The results show that the vaccination on a multiple cohort is more effective than a single cohort. Indeed, a major number of pre-cancerous lesions, cases of cancer, and related deaths are avoided. In a period of sharp decline in the health budget, investment in prevention seems to be the most reasonable choice in view of avoiding in the medium term pre-cancerous and cancerous lesions generating a significant expense. Our analysis places the extent of HPV vaccination among the measures that the regional decision-makers should put in place to maximize the efficiency of scarce resource.